THE ENTIRE FACE IRREGULARITY STRENGTH OF A BOOK WITH POLYGONAL PAGES - Tilukay, Meilin I.; Ilwaru, Venn Y. I. (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2015)
A face irregular entire labeling is introduced by Baca et al. recently, as a modification of the well-known vertex irregular and edge irregular total labeling of graphs and the idea of the entire colouring of plane graph. A face irregular entire k-labeling ðœ†:ð‘‰âˆªð¸âˆªð¹â†’{1,2,â‹¯,ð‘˜} of a 2-connected plane graph ðº=(ð‘‰,ð¸,ð¹) is a labeling of vertices, edges, and faces of ðº such that for any two different faces ð‘“ and ð‘”, their weights ð‘¤ðœ†(ð‘“) and ð‘¤ðœ†(ð‘“) are distinct. The minimum ð‘˜ for which a plane graph ðº has a face irregular entire ð‘˜-labeling is called the entire face irregularity strength of ðº, denoted by ð‘’ð‘“ð‘ (ðº). This paper deals with the entire face irregularity strength of a book with ð‘š ð‘›-polygonal pages, where embedded in a plane as a closed book with ð‘›âˆ’sided external face.